2022
DOI: 10.1039/d2ra00523a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced total flavonoid accumulation and alleviated growth inhibition of germinating soybeans by GABA under UV-B stress

Abstract: Effect of GABA on isoflavone metabolism in soybeans under UV-B treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, the exogenous GABA can pass through the cell membrane and enter the cell, stimulate hormone production, regulate growth and development, and further cause intracellular physiological and biochemical changes, thereby regulating polyphenols metabolism pathway gene expression to achieve the enrichment effect. Some studies have found that under UV-B stress, exogenous GABA can increase the activity of flavonoid synthase and the expression of related genes, inducing the accumulation of flavonoids [43] . Therefore, the increase in polyphenols content of mung beans can be attributed to the combined effect of GABA, ultrasonic, and germination treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the exogenous GABA can pass through the cell membrane and enter the cell, stimulate hormone production, regulate growth and development, and further cause intracellular physiological and biochemical changes, thereby regulating polyphenols metabolism pathway gene expression to achieve the enrichment effect. Some studies have found that under UV-B stress, exogenous GABA can increase the activity of flavonoid synthase and the expression of related genes, inducing the accumulation of flavonoids [43] . Therefore, the increase in polyphenols content of mung beans can be attributed to the combined effect of GABA, ultrasonic, and germination treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we speculated that K, P, and Ca play a role in the metabolic pathway of isoflavones during the early growth stages, resulting in elevated levels of isoflavonoid metabolites (genistein 7-O-beta-D-glucoside and daidzein). The enrichment of isoflavones can improve the adaptability of plants to unfavorable environments, including low temperatures, UV radiation, and heavy-metal stress (Ma et al, 2018;Veremeichik et al, 2021;Gu et al, 2022). This suggests that the application of K and P fertilizers during the development of S. japonica can enhance its environmental adaptability (Liu et al, 2017).…”
Section: Changes In the Inorganic Elements Of Fs In Different Stagesmentioning
confidence: 99%
“…In the isoflavonoid pathway, isoliquiritigenin is generated by condensation of 4-coumarate with CoA and 3-molonyl-CoA and transformed into daidzein. Daidzein is reduced and hydroxylated to produce (3R)-2′-hydroxydihydrodaidzein, the precursor of glycinol [ 33 , 43 , 44 ]. Finally, glyceollins I, II, and III are produced through the condensation of (-)-glycinol and prenyl diphosphate.…”
Section: Introductionmentioning
confidence: 99%